Teyonorenoplasty, Innovative Approaches in Surgical Practices - Komilov Javlonbek Ravshanbek o’g’li (Academia One Publishing, 2024)
This article focuses on the topic "Teynorinoplasty: Innovative Approaches in Surgical Procedures," exploring recent advancements in surgical practices. Teynorinoplasty, a surgical operation aimed at altering the shape of the nose and improving breathing, has solidified its place in modern medicine. The article examines the latest technologies and methods used in this procedure, including laser technology, 3D modeling, and robotic approaches. These innovative techniques not only enhance the efficiency of the surgery but also significantly shorten the patient's recovery time. Additionally, the article discusses the importance of ensuring patient safety, reducing postoperative complications, and improving cosmetic outcomes in these procedures.
Keywords: Teynorinoplasty; nasal surgery; innovative technologies; laser